Analisis Harga Pokok Penjualan AMDK ASA dan Dampaknya terhadap Strategi Penetapan Harga - Trisasi Maulanal Aziz (AKUNTANSI 45, 2026)
The growth of bottled drinking water (bottled water) industry in Indonesia is increasing rapidly as public awareness of the importance of Health and the availability of drinking water that is suitable for consumption. This condition also encourages very tight competition, especially with the dominance of big brands, and accompanied by challenges in the form of rising prices of raw materials and energy. The situation requires companies to manage production costs more efficiently and formulate appropriate pricing strategies. This study aims to examine the calculation of the cost of goods sold (cogs) of ASA AMDK products produced by Perum jasa Tirta I and assess their impact on pricing policy in 2024. The method used is qualitative with descriptive approach. Research Data were obtained through interviews with management and operational staff, direct observation in the field, as well as the review of documents in the form of financial statements and production data. The results showed that the largest cost component was still borne by raw materials, followed by direct labor, as well as overhead costs that increased due to machine depreciation loads and energy fluctuations. The main problem is found in the aspect of classification and allocation of overhead costs that are not fully accurate, so that it affects the accuracy of the cogs calculation. These inaccuracies have implications for pricing strategies, because the applied selling price can deviate from the actual cost, potentially suppressing profits and weakening competitiveness.